Anti-Inflammatory Effects of Protein Kinase Inhibitor Pyrrol Derivate - Halyna M. Kuznietsova; Maryna S. Yena; Iryna P. Kotlyar; Olexandr V. Ogloblya; Volodymyr K. Rybalchenko (The Scientific World Journal)
In our previous studies we showed antitumor and anti-inflammatory activities of protein kinases inhibitor pyrrol derivate 1-(4-Cl-benzyl)-3-Cl-4-(CF3-fenylamino)-1H-pyrrol-2,5-dione (MI-1) on rat colon cancer model. Therefore anti-inflammatory effect of MI-1 on rat acetic acid induced ulcerative colitis (UC) model was aimed to be discovered. The anti-inflammatory effects of MI-1 (2.7 mg/kg daily) compared to reference drug Prednisolone (0.7 mg/kg daily) after 14-day usage were evaluated on macro- and light microscopy levels and expressed in 21-grade scale. Redox status of bowel mucosa was also estimated. It was shown that in UC group the grade of total injury (GTI) was equal to 9.6 (GTIcontrol=0). Increase of malonic dialdehyde (MDA) by 89% and protein carbonyl groups (PCG) by 60% and decrease of superoxide dismutase (SOD) by 40% were also observed. Prednisolone decreased GTI to 3 and leveled SOD activity, but MDA and PCG remained higher than control ones by 52% and 42%, respectively. MI-1 restored colon mucosa integrity and decreased mucosa inflammation down to GTI = 0.5 and leveled PCG and SOD. Thus, MI-1 possessed anti-inflammatory properties, which were more expressed that Prednisolone ones, as well as normalized mucosa redox balance, and so has a prospect for correction of inflammatory processes.